Selective epitaxy of carbon-tetrachloride-doped GaAs grown by metalorganic chemical vapor deposition - Park, YK; Kim, SI; Kim, Y; Kim, EK; Min, SK; Son, CS; Choi, IH (KOREAN PHYSICAL SOC, 1998)
A selectively confined V-shaped carbon-tetrachloride-doped GaAs epilayer grown inside a U-groove by one-step growth has been successfully fabricated on a patterned GaAs substrate by atmospheric pressure metalorganic chemical vapor deposition. A dramatic lateral growth enhancement was obtained by supplying carbon tetrachloride and allowed selective epitaxy. This one-step maskless selective epitaxy does not require any masking material. The selective epitaxy has also been demonstated in a U-shaped groove array.
Keywords: QUANTUM-WIRE STRUCTURES; FABRICATION; REGROWTH; LAYER; ARRAY; DOTS